Antioxidant capacity and sustainability of Saccharomyces cerevisiae cells exposed to ozone - Goriacha, I.P.; Zinchenko, V.D.; Dyubko, T.S.; Romodanova, E.A.; Tatarets, A.L. (Вiopolymers and Cell, 2014)
Aim. The investigation of response of S. cerevisiae cells to the effect of ozone in different doses and determination of total antioxidant capacity (TAC) of these cells. Methods. TAC was estimated with the chemiluminescent method when introducing ozone into S. cerevisiae cells. The damage of cells was determined by the methods of fluorescent microscopy and flow cytometry using fluorescent dye Square-460. Results. It was shown that under the ozone dosed administration into the S. cerevisiae cells suspension the chemiluminescence flash occurred in response to each new ozone doze. The flash amplitude slightly changes under low doses and decreases after achieving some total ozone dose, being characteristic for these cells. At the same time the damaged cells appear, the number of which augments with increasing the administered ozone dose. Conclusions. We assessed the TAC of S. cerevisiae cells, as the ozone dose, which may be neutralized by the systems of their antioxidant protection: 240 ± 20 nmol/106 cells. The S. cerevisiae cells are resistant to the effect of excessive ozone until its doses exceed the TAC value for these cells. Мета. Дослідження реакції клітин S. сerevisiae на дію озону в різних дозах і визначення загальної антиоксидантної ємності (ЗАОЄ) даних клітин. Методи. ЗАОЄ визначали хемілюмінесцентним методом за введення озону в клітини S. сerevisiae. Пошкодження клітин виявляли методами флуоресцентної мікроскопії та проточної цитофлуориметрії із застосуванням флуоресцентного барвника Square-460. Результати. Показано, що за дозованого введення озону у суспензію клітин S. сerevisiae виникає спалах хемілюмінесценції у відповідь на кожну нову дозу озону. Амплітуда спалаху мало змінюється за низьких доз і знижується після досягнення деякої характерної для даних клітин сумарної дози озону. При цьому з’являються пошкоджені клітини, кількість яких збільшується з ростом дози введеного озону. Висновки. Оцінено ЗАОЄ клітин S. сerevisiae як дозу озону, яку здатні нейтралізувати системи їхнього антиоксидантго захисту, що становить 240 ± 20 пмоль/106 кл. Клітини S. сerevisiae є стійкими до дії надлишкового озону за його доз, які не перевищують величину ЗАОЄ даних клітин. Цель. Исследование реакции клеток S. cerevisiae на действие озона в различных дозах и определение общей антиоксидантной емкости (ОАОЕ) данных клеток. Методы. ОАОЕ определяли хеми- люминесцентным методом при введении озона в клетки S. сerevisiae. Повреждение клеток озоном выявляли методами флуоресцентной микроскопии и проточной цитофлуориметрии с использованием флуоресцентного красителя Square-460. Результаты. Показано, что при дозированном введении озона в суспензию клеток S. сerevisiae возникают вспышки хемилюминесценции в ответ на каждую новую дозу озона. Амплитуда вспышки мало изменяется при низких дозах и снижается после достижения некоторой характерной для данных клеток суммарной дозы озона. При этом появляются поврежденные клетки, количество которых увеличивается с ростом дозы введенного озона. Выводы. Оценена ОАОЕ клеток S. сerevisiae как доза озона, которую способны нейтрализовать системы их антиоксидантной защиты, она составляет 240 ± 20 пмоль/106 кл. Клетки S. cerevisiae устойчивы к действию избыточного озона при его дозах, не превышающих величину ОАОЕ данных клеток.